Essay in Quran on the Issue of Fetal Sex Determination and Morality with the Approach of Elimination of Science and Religion Conflicts - Mahdi Misaghi Nezhad; Morteza Abdoljabari; Masud Moslemifard Khaledi; Marzieh Karamkhani (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Human knowledge is a gift of God and according to the evidences, it can achieve mysterious things thus in addition to proving the Noblest of all creatures, can have apparently conflicts with some verses of the Quran. According to divine verses, God determines fetal gender and it seems sex determination is outside of human control. But today, medical and genetic advances on the one hand and possibility of violation of ethical principles and risks caused in the area of moral and social health on the other hand, have made it a serious challenge in science and religion. The religious perspective can teach a targeted program to make a better human life; a program that according to the progress and development of science, with good performance in behavioral patterns, will justify and frame human intervention in the field of medicine and sex determination. Therefore, in this article, along with an explanation of the issue of sex determination and providence, the human intervention, and its alignment with the religion and relation with mental and social health have been expressed. Keywords:Science, Authority, Health, Morality For downloading the full-text of this article please click here.